Field‐Aligned Low‐Energy O+ Flux Enhancements in the Inner Magnetosphere Observed by Arase. Issue 8 (29th July 2021) - Nosé, M.; Matsuoka, A.; Miyoshi, Y.; Asamura, K.; Hori, T.; Teramoto, M.; Shinohara, I.; Hirahara, M.
Abstract: The present study examines the low‐energy ion flux variations observed by the Arase satellite in the inner magnetosphere. From the magnetic field and ion flux data obtained by the fluxgate magnetometer and the low‐energy particle experiments–ion mass analyzer onboard Arase, we find 55 events of the low‐energy O + flux enhancement accompanied with magnetic field dipolarization in the periods of April 1–October 31, 2017 and July 1, 2018–January 31, 2019. The low‐energy O + flux enhancements (a) start a few minutes after the dipolarization onset, (b) have energy‐dispersed signatures with decreasing energy from a few keV down to ∼10 eV, (c) are observed in both storm and non‐storm periods, (d) have a field‐aligned distribution ( α  ∼ 0° in the southern hemisphere and α  ∼ 180° in the northern hemisphere), (e) are accompanied by the low‐energy H + flux enhancements that have lower energies than O + by a factor of 3–10, and (f) increase the O + density and the O + /H + density ratio by ∼10 times and 4–5 times, respectively. We perform a numerical simulation to trace ion trajectories forward in time from the Arase positions. It is revealed that both H + and O + ions drift eastward and reach the dawn‐to‐morning sector without being lost in the ionosphere, if the pitch angle scattering effect is considered near the equatorial plane. This result suggests that these low‐energy field‐aligned ions can contribute to formation of the warm plasma cloak. Key Points: O + flux enhancements that have energy‐dispersed signatures at <∼5 keV appear a few minutes after magnetic field dipolarization The lowest energy of ∼10 eV and a field‐aligned distribution of the O + flux enhancements suggest prompt extraction from the ionosphere The field‐aligned low‐energy O + flux enhancements can be a source of the warm plasma cloak